Caracterização microbiológica de ovos de consumo e de carcaças de frangos produzidos no Estado de Minas Gerais - Liliane Denize Miranda Menezes (2013)
A total of 672 samples of in natura eggs and 240 samples of chicken carcasses were collected at federally and state-inspected establishments from the five regions of Minas Gerais - Brazil - with the aim of evaluating their microbiological quality. All egg samples were submitted to counts of aerobic mesophilic microorganisms, coliforms at 35°C and 45°C, coagulase-positive and negative Staphylococcus spp., molds and yeasts and also isolation of Salmonella spp. All samples of chicken carcasses were submitted to counts of coliforms at 35°C and 45°C and isolation of Staphylococcus spp., Campylobacter spp., Listeria monocytogenes, E. coli O157:H7 and Salmonella spp. Egg analyses showed low counts of all bacteria as well as absence of Salmonella spp. However, 34.2% of chicken carcasses were contaminated by 35°C coliforms, 13% by 45°C coliforms; all samples tested positive for Staphylococcus spp., 9.1% to Salmonella spp., 15.5% to Listeria monocytogenes and 2.1% for Campylobacter spp. E. coli O157:H7 was not isolated from the samples. Thus, it was concluded that the analyzed eggs had appropriated microbiological quality but high counts of microorganisms found in chicken carcasses may represent a risk to the health of consumers.